TEACHERS’ STRATEGY IN IMPLEMENTING ENGLISH CURRICULUM IN A JUNIOR HIGH SCHOOL IN INDONESIA - Intansari, Raden (Indonesian Journal of Applied Linguistics, 2013)
Abstract: This study is a part of a bigger study investigating teachers’ personal theories (beliefs) regarding English teaching and learning. Involving forty-two English teachers of fifteen Junior High Schools in the city of Sukabumi, West Java, this cross-sectional survey study used data gained from an open-ended questionnaire. A total of 3696 raw data items were gathered and analyzed both qualitatively and quantitatively. Relevant findings regarding the implementation of the curriculum in the daily process of English teaching and learning show that there are gaps between the mandated curriculum as stipulated by the government and the implemented curriculum at the classroom level. This departure from the mandated curriculum, in turn, diverts the course of curriculum implementation and leads to a level of accomplishment of the main goals of the English teaching and learning, which is different from what is stated in the mandated curriculum.